Immunomodulatory activities of alpha lipoic acid with a special focus on its efficacy in preventing miscarriage. (1st December 2016) - Monastra, Giovanni; De Grazia, Sara; Cilaker Micili, Serap; Goker, Asli; Unfer, Vittorio
ABSTRACT: Introduction : Alpha lipoic acid (ALA) is an essential mitochondrial co-factor and, as a free molecule, it can exert multi-level immunomodulatory functions. Both ALA and its reduced form, dihydrolipoic acid (DHLA), are believed to be able to chelate heavy metals, to regenerate essential antioxidants and to repair important molecules damaged by oxidation. The largest part of the effects of ALA/DHLA couple can be explained by a specific stimulatory activity on Nrf2-dependent gene transcription and by the inhibition of NF-kB activity. These features have prompted its use as a drug for several diseases. Areas covered : This article surveys the main features of ALA/DHLA and its therapeutic effects. Its complex and differentiated function cannot simply be reduced to anti-inflammatory, antioxidant and detoxifying action. We highlight its capability to finely modulate several physiological pathways when unbalanced. In particular, we focus our attention on pregnancy, in relation to ALA administration by oral route and by a new formulation for vaginal delivery, in patients with threatened miscarriage. Expert opinion : Future efforts should be devoted to explaining carefully ALA/DHLA mechanism of action to reactivate the physiological balance when modified during pregnancy. On the other hand, ALA safety in pregnant women and its pharmacokinetics by vaginal route, have to be studied in depth. Moreover, ALA efficacy has to be confirmed in a much larger sample of patients.